FACTORS AND ASSESSMENT METHODS IN THE DEVELOPMENT OF HR BRANDING: FOREIGN EXPERIENCE (Scientific electronic journal "Labor Economics and Human Capital", 2024)
In the article, modern trends and influencing factors in the development of HR branding, HR branding development factors in the cited studies, methods of forming a positive image of the organization, a system of measures for strategic management of the organization, methods of evaluating the effectiveness of HR branding in the enterprise and a number of other aspects are shown. researched and analyzed. Within the framework of the article, the definition of the essence of the concept of HR brand, review of the main stages of the branding process of organizations, development of the image of the organization by defining and classifying the benefits provided by the HR brand, analysis of existing approaches to the evaluation of the HR brand, and creation of a system for evaluating the economic efficiency of the organization are presented. recommendations of experts are presented.
Keywords: HR branding, modern trends, development factors, organization, positive image, methods, organization, strategic management, system of measures, enterprise, efficiency, evaluation.